Implementation of Augmented Reality (AR) Technology in English Learning - Oktadela, Resy; Elida, Yusti; Ismail, Syofianis; Hartono, Wira Jaya (Journal of English Language and Education, 2023)
This study aims to use of augmented reality-based learning media to improve elementary school students' critical thinking skills and digital literacy. This research method was Research and Development (RD) with the ADDIE model. The research results showed: (1) the analysis stage was carried out by media, curriculum, and material analyses as guidelines for efficient and effective media design; (2) the design stage was carried out by designing an augmented reality media framework and making research instruments; (3) the development stage was carried out by developing the design of learning media and research instruments, assessments from experts with very decent results and revising the media based on criticism and suggestions; (4) the implementation stage was carried out through AR media development trials and pretest-posttest analysis of critical thinking skills and digital literacy using normality test, N-gain score, and independent t-test; and (5) the evaluation stage was carried out with the final revision and analysis of student response questionnaires which indicated that the level of practicality of the product was categorized as very practical. This research concluded that AR media effectively improved elementary school students' critical thinking skills and digital literacy.